2014
DOI: 10.1371/journal.pone.0092877
|View full text |Cite
|
Sign up to set email alerts
|

The Geogenomic Mutational Atlas of Pathogens (GoMAP) Web System

Abstract: We present a new approach for pathogen surveillance we call Geogenomics. Geogenomics examines the geographic distribution of the genomes of pathogens, with a particular emphasis on those mutations that give rise to drug resistance. We engineered a new web system called Geogenomic Mutational Atlas of Pathogens (GoMAP) that enables investigation of the global distribution of individual drug resistance mutations. As a test case we examined mutations associated with HIV resistance to FDA-approved antiretroviral dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Second, the platform integrates mapping of geographical locations for genomes from a large database. Available software for mapping geolocations of pathogen genomes includes Supramap, which superimposes phylogenies onto a map [ 16 ], and GoMap, which is currently implemented to map HIV strains with drug resistance mutation information [ 17 ]. Unlike these, the Pathogen Metadata Platform links mapping with all samples from BioSample, though without a DNA analysis component.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the platform integrates mapping of geographical locations for genomes from a large database. Available software for mapping geolocations of pathogen genomes includes Supramap, which superimposes phylogenies onto a map [ 16 ], and GoMap, which is currently implemented to map HIV strains with drug resistance mutation information [ 17 ]. Unlike these, the Pathogen Metadata Platform links mapping with all samples from BioSample, though without a DNA analysis component.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, we re‐focus briefly on geogenomics' origins in Baker et al (2014) and the counterpoint of Sargeant et al (2014) as food for thought. Whereas Sargeant et al (2014) appeared largely an extension of existing practice, Baker et al (2014) joined a chorus for updating and extending phylogeography sensu lato (Dawson, 2014; Hickerson et al, 2010; Knowles & Maddison, 2002; Marske et al, 2013; Papadopoulou & Knowles, 2016), and perhaps because Baker et al (2014) expounded a new core idea and identified a specific audience, it had greater impact. Yet, many papers in the special issue include components that are not encapsulated by the original definition of geogenomics ( sensu Baker et al, 2014), as they do not test or constrain specific geological hypotheses, but use geological data to build predictions about biological processes (e.g.…”
Section: Figurementioning
confidence: 99%
“…Intriguingly, Sargeant et al (2014) also coined the term ‘geogenomics’ but from a very different perspective, specifically the geography of pathogens, and emphasizing finer spatial and temporal scales. Sargeant et al (2014) defined geogenomics as the ‘examin[ation of] the geographic distribution of … genomes … with a particular emphasis on those mutations that give rise to [adaptations]’; their vision of geogenomics was an extension of evolutionary biology, historical and phylogenetic biogeography, and phylogeography. The differences between these two visions—one explicitly hypothesis driven (Baker et al, 2014), and the other largely descriptive (Sargeant et al, 2014)—and their fates are perhaps illuminating: Baker et al (2014) has been well cited (Figure 1), whereas Sargeant et al (2014) has been cited only once.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations